2014
DOI: 10.1017/s096856501400002x
|View full text |Cite
|
Sign up to set email alerts
|

Informal rural credit markets and interlinked transactions in the district of late Ottoman Haifa, 1890–1915

Abstract: By examining the acts of the Public Notary of Haifa (1890–1915), this article shows that it was the traditional informal market of credit, run by local notables, which financially supported the development of the small-landholding-based agricultural sector of the Haifa district in late Ottoman Palestine. In seeking to ascertain what led to the success of the informal rural credit market as compared with the formal credit market, the article finds that the local notables, who acted as financial intermediaries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Recent research has also focused on the structure and size of non-ecclesiastical sources of credit, evidencing how, during the late colonial period, there was an expansion of merchant credit flows and the sophistication of financial tools (Ibarra 2017; Cascavita 2021; Gutiérrez and Torres 2021; Torres 2014, 2021). In line with new research on European and Asian economies, the literature has also shown that pre-industrial credit markets were more dynamic and larger in GDP than previously thought (Hoffman et al 1999, 2015; Ito 2013; Ecchia 2014).…”
supporting
confidence: 60%
“…Recent research has also focused on the structure and size of non-ecclesiastical sources of credit, evidencing how, during the late colonial period, there was an expansion of merchant credit flows and the sophistication of financial tools (Ibarra 2017; Cascavita 2021; Gutiérrez and Torres 2021; Torres 2014, 2021). In line with new research on European and Asian economies, the literature has also shown that pre-industrial credit markets were more dynamic and larger in GDP than previously thought (Hoffman et al 1999, 2015; Ito 2013; Ecchia 2014).…”
supporting
confidence: 60%
“…Recent works argue that legal and cultural institutions are only properly understood in conjunction with the political economy in which they formed. Examples include Barakat 2019; Kostopoulos 2016; Svetla Ianeva, Guild and non-guild labour in the Central Balkans during the nineteenth century, in Papastefanaki and Potamianos 2021, 131–153; Ecchia 2014; and Christos Hadziiosif, The invisible army of Greek labourers, in Papastefanaki and Kabadayı 2020, 113–148.…”
mentioning
confidence: 99%
“…26–9; Ianeva 2009). In her study on the credit market of nineteenth-century Haifa, Ecchia (2014) also shows that local notables were able to strengthen their position in the loan market through informal connections despite the expansion of banking institutions in the region. Interestingly, a number of reports on moneylending in the Ottoman lands prepared by imperial bureaucrats in the 1830s reached the same conclusion.…”
mentioning
confidence: 99%